IoET: From Paradox To Paradigm - Kumar Yogi, Manas; Uma, Darapu; Mahesh Kumar, K; Bhanu Prakash, P (International Journal of Engineering and Technology, 2018)
The current importance and future promises of the Internet of Things(IoT), Internet of Everything(IoET) are diligently discussed in this paper. The analysis clearly distinguishes between IoT and IoET which are mostly considered to be the same by novices. Upon examining the current advancement in the fields of IoT, IoET, the paper presents scenarios or the possible future expansion of their applications also considering security aspects as same.Â Â